2017
DOI: 10.1186/s12882-017-0731-2
|View full text |Cite
|
Sign up to set email alerts
|

The association of obstructive sleep apnea and renal outcomes—a systematic review and meta-analysis

Abstract: BackgroundThe aim of this systematic review and meta-analysis was to summarize the association of obstructive sleep apnea (OSA) with renal outcome.MethodsOur study followed the PRISMA guidelines. Two independent reviewers searched for relevant articles in the databases of Pubmed, the Web of Science and CENTRAL, and conducted study selection and quality assessment. A random-effect model was used to estimate the effects.ResultsA total of 1240 articles were initially identified (Pubmed = 568, Web of Science = 640… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 58 publications
1
22
0
1
Order By: Relevance
“…Our previous study showed that cystatin C, a novel biomarker of kidney impair, was increased in patients with an apnea-hypopnea index of more than 30 events/hour [ 4 ]. A systematic review and meta-analysis concluded the significant association between OSA and higher albuminuria/proteinuria and a lower estimated glomerular filtration rate [ 19 ]. A study indicates that CPAP treatment can improve renal hemodynamics and the downregulation of the renal renin-angiotensin system in OSA patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed that cystatin C, a novel biomarker of kidney impair, was increased in patients with an apnea-hypopnea index of more than 30 events/hour [ 4 ]. A systematic review and meta-analysis concluded the significant association between OSA and higher albuminuria/proteinuria and a lower estimated glomerular filtration rate [ 19 ]. A study indicates that CPAP treatment can improve renal hemodynamics and the downregulation of the renal renin-angiotensin system in OSA patients [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a major risk factor of OSAS [1,2,3,4,5,6,7], and both of these conditions impose adverse neurocognitive, mood, behavioral, cardiovascular, and metabolic consequences in both children and adults. In addition, as the awareness and consequently the frequency of diagnosing OSAS have increased, a large list of additional OSAS-associated morbidities has been reported, including chronic kidney disease, erectile dysfunction, ocular conditions, Alzheimer disease, nocturia, and even cancer in adults, while in children enuresis and bruxism are frequent adverse consequences [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31]. Efforts are ongoing to develop new and more effective therapies for OSAS based on underlying mechanisms promoting upper airway collapsibility during sleep [32,33].…”
Section: Obstructive Sleep Apnea Syndrome (Osas) and Morbiditymentioning
confidence: 99%
“…Также особую группу пациентов составляют пациенты с обструктивным апноэ сна. Развитие респираторных осложнений у данной группы больных происходит в 2 раза чаще, чем у остальных [10]. Использование опиоидных анальгетиков может приводить к явлениям обструкции, удлиняя продолжительность эпизодов обструктивного апноэ сна [11,12].…”
Section: о б з о р ыunclassified